Revitalisasi Fungsi Madrasah Diniah Sebagai Sarana Pendidikan Agama Islam - Arifin, Zainal (TAAWUN, 2024)
This service program aims to revitalize the function of The Madin Takmiliyah Roudhotul ‘Ulum as a nonformal Islamic education facility that is relatively complete in teaching various Islamic religious disciplines compared to TPQ and to increase the interest of Karang Village residents to send their children to madin after passing TPQ. The research method is participatory action research (PAR) where participant involved to solve problems faced by society. The activity program stages include collecting data related to the root of the problem of the decline in the vitality of the functioning of the Madin through in-depth interviews with various parties involved, namely: the teacher council, religious leaders, student guardians, and the village government. After finding the root of the problem, a program of participatory activities was prepared which included village deliberations with the agenda of restructuring the management of Madin, aligning the curriculum of Madin, and positioning the TPQ. The results of the activity program are the building of awareness among residents about the importance of sending their children to Madin after passing the TPQ so that in turn this awareness can maintain the continuity of Madin and strengthen its function as a non-formal educational institution to deepen knowledge of the Islamic religion which is relatively inadequately studied or taught in formal educational institutions or institutions. non-formal education in the form of TPQ.